Does Helicobacter pylori infection have a role in coronary artery disease? - Ahmet AYDIN; Rukiye VARDAR; Harun EVRENGÜL; Mehmet UNGAN; Mustafa YILMAZ; Serdar PAYZIN (Turkish Journal of Gastroenterology, 2019)
-